Estudo dos efeitos fisiopatológicos e moleculares do knockdown do gene CG15105 em cérebro de Drosophila melanogaster - Silva, Matheus Henrique (2022)
Neurodegeneration is a pathophysiological process leading to an impaired nervous system, it is caused by cumulative damage over a lifetime and it is commonly related to aging. With the increase in life expectancy of the world population, the study of neurodegeneration has become a world priority. Alzheimer's disease is one of the most common neurodegenerative diseases. A pathophysiological event of this disease is the accumulation of the β-amyloid peptide, caused by the imbalance between production and degradation. The accumulation of β-amyloid is related to other alterations such as the expression reduction of gene CG15105 (tn), which encode proteins involved in protein degradation processes through ubiquitination. In this way, the present work aimed to explore the effects of the CG15105 gene on the brain of Drosophila melanogaster. Through the use of the technique of genetic knockdown with iRNA in the brain of flies and histopathological and behavioral analyses it was observed that the knockdown of CG15105 gene reduce locomotor activity, and the knockdown of CG15105 causes morphological degeneration of brain. And the findings of the in silico studies of the CG15105 show that its activity is mainly related to ubiquitination. And some of the genes in the CG15105 interaction network that have cytoskeleton functions present transcriptional alterations in the brain of flies related to aging processes and the presence of the β-amyloid peptide.